General Characteristic of the Concept and Featuresof the Constitutional Regime - R. G. Nurmagambetov (Сибирское юридическое обозрение, 2018)
This article analyzes the concept and features of the constitutional regime in the Russian Federation, in particular, its content is disclosed. Analyzing the concepts of “legal regime” and “constitutional legal regime”, the Author proposes his own definition of the constitutional regime. In the article, special attention is given to the characterizing of signs and grounds for classifying the constitutional regime. Thus, he refers to the number of types of constitutional regime material and procedural, regulative and protective, permanent and temporary; the constitutional regime of foreign citizens, stateless persons, citizens, political parties, other associations of citizens, the constitutional regime for the functioning of federal, regional and municipal authorities, as well as the constitutional regime of the status of subjects of the federation, direct and indirect, to the ordinary constitutional regime, emergency and martial law.